Disaster education and management : a joyride for students, teachers and disaster managers - Bhandari, Rajendra Kumar (Springer India, 2014)
The book is expressly written for the young minds because they are our best hope for a safer tomorrow. The book is profusely illustrated, as it offers a joyride to the world of the whole range of hazards through simplified teaching-learning process, with less of teaching and more of learning. This is because most readers would love to learn without actually being taught. The book is designed to take advantage of distilled wisdom of centuries to inspire and enlighten the common man to turn them into prime movers of safer societies. Senior citizens, community leaders, self-trained disaster managers, social workers, media personnel, bureaucrats and those averse to the very thought of reading will also find the book useful as it is illustrative and inviting.